2019
DOI: 10.1101/847376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linked networks reveal dual roles of insect dispersal and species sorting for bacterial communities in flowers

Abstract: Due to the difficulty of tracking microbial dispersal, it rarely possible to disentangle the relative importance of dispersal and species sorting for microbial community assembly. Here, we leverage a detailed multilevel network to examine drivers of bacterial community assembly within flowers. We show that plant species with similar visitor communities tend to have similar bacterial communities, and visitor identity to be more important than dispersal rate in structuring floral bacterial communities. However, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Lactobacilli are associated with key roles in pollen fermentation and defense against bacterial pathogens [ 66 ], possibly by secreting antimicrobial substances [ 67 ]. In our case, the lactobacilli found in high abundances for the deceased larvae might have originated from other bees via flowers [ 30 , 32 , 65 , 68 , 69 ]. They might then thrive on the large amounts of available organic pollen resources in the absence of an Osmia bicornis larvae and its microbial associates, which could both compete with and suppress Lactobacillus in the nest [ 52 , 59 , 70 ].…”
Section: Discussionmentioning
confidence: 80%
“…Lactobacilli are associated with key roles in pollen fermentation and defense against bacterial pathogens [ 66 ], possibly by secreting antimicrobial substances [ 67 ]. In our case, the lactobacilli found in high abundances for the deceased larvae might have originated from other bees via flowers [ 30 , 32 , 65 , 68 , 69 ]. They might then thrive on the large amounts of available organic pollen resources in the absence of an Osmia bicornis larvae and its microbial associates, which could both compete with and suppress Lactobacillus in the nest [ 52 , 59 , 70 ].…”
Section: Discussionmentioning
confidence: 80%
“…Conversely, if specialists interact with the same plants as generalists do, both classes of bees may be exposed to the same microbes. The microhabitats of specialist and generalist bee pollen provisions may filter different microbes based on pollen and nectar chemistry, altering microbial composition as has been found with nectar microbial communities [20]. Comparing the pollen-provision microbial communities of closely related specialist and generalist bees will help address how diet breadth affects microbe exposure and establishment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that plant communities with a similar floral visitor community have similar microbes (Rebolleda Gómez & Ashman, 2019;Zemenick et al, 2019). However, they found that while flowers were hubs for arthropod visitation, flowers did not necessarily serve as hubs for microbes, which suggests a degree of host sorting (Zemenick et al, 2021) which supports the idea that floral visitors shape microbial communities. However, little is known regarding how this could impact fruit microbial communities.…”
Section: Introductionmentioning
confidence: 89%
“…Fruit and flowers are especially warranted to studies at finer spatial scales, as pollinator interactions are most likely to impact these tissues (Rebolleda-Gómez et al, 2019;Ushio et al, 2015;Zemenick et al, 2021). Recent studies found that plant communities with a similar floral visitor community have similar microbes (Rebolleda Gómez & Ashman, 2019;Zemenick et al, 2019).…”
Section: Introductionmentioning
confidence: 99%